Identification and characterization of the chalkiness endosperm gene CHALK-H in rice (Oryza sativa L.) - Ri-hua PIAO; Mo-jun CHEN; Fan-mei MENG; Chun-yan QI; Hee-jong KOH; Meng-meng GAO; An-qi SONG; Yong-mei JIN; Yong-feng YAN (Journal of Integrative Agriculture)
Chalkiness is one of the most important agronomic traits in rice breeding, which directly affects the quality of rice seed. In this study, we identified a chalkiness endosperm mutant, chalk-h, from N-methyl-N-nitrosourea (MNU)-induced japonica rice cultivar Hwacheong (HC). Compared with wild type (WT)-HC, chalk-h showed severe chalkiness in the endosperm, yellowish green leaves, as well as reduced plant height. Scanning electron microscopy (SEM) analysis showed that starch grains in the chalk-h mutant were irregular in size and loosely arranged, with large gaps between granules, forming ovoid or orbicular shapes. MutMap analysis revealed that the phenotype of chalk-h is controlled by a single recessive gene LOC_Os11g39670 encoding seryl-tRNA synthetase, which is renamed as CHALK-H. A point mutation occurs in chalk-h on the sixth exon (at nucleotide 791) of CHALK-H, in which adenine (A) is replaced by thymidine (T), resulting in an amino acid codon change from glutamine (Glu) to valine (Val). The chalk-h mutant exhibited a heat-sensitive phenotype from the 3-leaf stage, including yellow-green leaves and reduced pigment content. The transcriptional expression of starch synthesis-related genes was down-regulated in the chalk-h mutants compared to WT-HC at different grain-filling stages. With an increase in temperature, the expression of photosynthesis-related genes was down-regulated in the chalk-h mutant compared to WT-HC. Overexpression of CHALK-H rescued the phenotype of chalk-h, with endosperm and leaf color similar to those of WT-HC. Our findings reveal that CHALK-H is a causative gene controlling chalkiness and leaf color of the chalk-h mutant. CHALK-H is the same gene locus as TSCD11, which was reported to be involved in chloroplast development under high temperature. We suggest that CHALK-H/TSCD11 plays important roles not only in chloroplast development, but also in photosynthesis and starch synthesis during rice growth and development, so it has great application potential in rice breeding for high quality and yield.